Antileishmanial activity and cytotoxicity of ZnO-based nano-formulations - Nazir S (Dove Medical Press, 2019)
Samina Nazir,1 Atiya Rabbani,2 Khalid Mehmood,3 Farhana Maqbool,4 Ghulam Mujtaba Shah,4 Muhammad Fiaz Khan,5 Muhammad Sajid2 1Department of Chemistry, College of Science, King Faisal University, Al-Ahsa, Saudi Arabia; 2Department of Biochemistry, Hazara University, Mansehra, Pakistan; 3Medical Centre, Quaid-e-Azam University, Islamabad, Pakistan; 4Department of Microbiology, Hazara University, Mansehra, Pakistan; 5Department of Zoology, Hazara University, Mansehra, PakistanCorrespondence: Muhammad SajidDepartment of Biochemistry, Hazara University, Mansehra, PakistanTel +92 333 507 1757Fax +92 99 741 4111Email sajid931@hotmail.comIntroduction: Nanoparticles (NPs) can be toxic due to their nano-range sizes. Zinc oxide (ZnO) has good biocompatibility and is commercially used in cosmetics. Moreover, ZnO NPs have potential biomedical uses, but their safety remains unclear.Methods: A range of doped ZnO NPs was evaluated for antileishmanial activity and in vitro toxicity in brine shrimp and human macrophages, and N-doped ZnO NPs were evaluated for in vivo toxicity in male BALB/C mice. N-doped ZnO NPs were administered via two routes: intra-peritoneal injection and topically as a paste. The dosages were 10, 50, and 100 mg/kg/day for 14 days.Results: Topical administration was safe at all dosages, but intra-peritoneal injection displayed toxicity at higher doses, namely, 50 and 100 mg/kg/day. The pathological results for the i.p. dose groups were mild to severe degenerative changes in parenchyma cells, increases in Kupffer cells, disappearance of hepatic plates, increases in cell size, ballooning, cytoplasmic changes, and nuclear pyknosis in the liver. Kidney histology was also altered in the i.p. administration group (dose 100 mg/kg/day), with inflammatory changes in the focal area. We associate pathological abnormalities with the presence of doped ZnO NPs at the diseased site, which was verified by PIXE analysis of the liver and kidney samples of the treated and untreated mice groups.Conclusion: The toxicity of the doped ZnO NPs can serve as an essential determinant for the effects of ZnO NPs on environmental toxicity and can be used for guidelines for safer use of ZnO-based nanomaterials in topical treatment of leishmaniasis and other biomedical applications.Keywords: ZnO, nanoparticles, doped-ZnO, NP toxicity, in vivo toxicity